Urgensi Penguatan Nilai-Nilai Religiusitas dalam Kehidupan terhadap Akhlak Mahasiswa Institut Agama Islam Bakti Negara Tegal - Roikhatul Jannah (La-Tahzan: Jurnal Pendidikan Islam, 2026)
This research aims to explore the urgency of strengthening religious values ??in student life and its influence on the formation of student morals at the Tegal State Bakti Islamic Institute. The research method used is a qualitative descriptive study with a phenomenological approach. Data was collected through in-depth interviews with students from various backgrounds and religious beliefs, as well as observations of religious activities on campus. The research results show that religious practices such as routine worship (congregational prayer, sunnah fasting), religious studies, istighosah, and active participation in the activities of the Junudul Mushtofa Student Activity Unit play a crucial role in forming students' moral awareness, integrity and empathy. The religious values ??internalized through these activities include compassion, peace, forgiveness, responsibility as caliph on earth, and social solidarity. These findings reinforce that strengthening the value of religiosity provides a solid spiritual foundation for the formation of noble morals in students, both in the vertical aspect (relationship with God) and the horizontal aspect (relationship with others and the environment). Research implications this research encourages the systematic integration of religious values ??into the tertiary education curriculum and the creation of a religious culture on campus as a strategy to strengthen student morals. However, this research is limited to one institution and relatively homogeneous participants, so the results cannot be generalized to a wider population.